TEORI MYOPIC LOSS AVERSION: SEBUAH TELAAH KEUANGAN KEPERILAKUAN INVESTASI INVESTOR DI PASAR MODAL - Riskin Hidayat (FE Program Studi Manajemen, 2017)
This paper aims to examine more about the theory of Myopic Loss Aversion which is one of thetheories of financial behavior. This is important because the study on financial behavior is stilllimited, especially about Myopic Loss Aversion. The Myopic Loss Aversion (MLA) theoryexplains the behavior of investors in risky investment decision-making processes in the stockmarket. Myopic Loss Aversion describes a combination of two theories, namely loss aversionand mental accounting. Loss aversion explains the fact that a person will tend to be moresensitive to losses than the profit earned. Someone to be loss averse if his caution is morefocused on losses than on gains. Mental accounting refers to a set of cognitive actionsundertaken by economic actors in managing, evaluating and maintaining its financial activities.So this paper is expected to provide additional insight knowledge about financial behavior.Keyword: finanial behavior, myopic loss avertion, mental accounting